1) -3q - (8p - 3q) = -3q - 8p + 3q = -8p
2) (2 + 3a) + (7a - 2) = 2 + 3a + 7a - 2 = 10a
3) - (11a + b) - (12a - 3b) = -11a - b - 12a + 3b = -23a + 2b
4) a + (a - 10) - (12a - 3b) = a + a - 10 - 12a + 3b = -10a + 3b - 10
5) (6x - 8) - 5x - (4 - 9x) = 6x - 8 - 5x - 4 + 9x = 10x - 12
1) -3q - (8p - 3q) = -3q - 8p + 3q = -8p
2) (2 + 3a) + (7a - 2) = 2 + 3a + 7a - 2 = 10a
3) - (11a + b) - (12a - 3b) = -11a - b - 12a + 3b = -23a + 2b
4) a + (a - 10) - (12a - 3b) = a + a - 10 - 12a + 3b = -10a + 3b - 10
5) (6x - 8) - 5x - (4 - 9x) = 6x - 8 - 5x - 4 + 9x = 10x - 12